Influência de El Niño e La Niña nas abundâncias de larvas de peixes migradores em uma região sob influência de barragens - Silva, Rafael Olímpio (2021)
Some environmental variables, such as rainfall, act as a trigger to encourage the reproduction of migratory fish. The El Niño Southern Oscillation (ENOS) is a natural phenomenon that directly influences the intensity of rainfall, where in the negative phase (La Niña) the rains are generally below the climatological normal and in the positive phase (El Niño) the rains are above normal , however its effects can be minimized due to the presence of dams in the rivers. The objective of this work was to evaluate the possible relationship between ENSO and the reproduction of some migratory species, through the analysis of larvae abundance, in a region under the influence of a dam. The analyzed material was collected in 18 points of the Ilha Grande National Park Region, obtained between the years 2006 and 2018, divided into 20 periods. The collections were carried out with the aid of plankton nets and the captured larvae were identified and classified. The ENSO numerical data were represented by the Niño Ocean Index. The relationship between migratory fish larvae densities and El Niño and La Niña events shows the influence of these phenomena on the spawning of these species, even in an environment where the fluviometric level is controlled by dams, confirming our hypothesis. The statistical significance presented between the highest capture densities and the El Niño event also show the importance of this phenomenon for the reproduction of migratory fish, in addition to pointing out rainfall as the main modulatory factor in the spawning of these species.